Research on Early Childhood Education policies: bibliographic memory, database and epistemology (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2021)
This paper falls within the research field on research and introduces reflections that seek to bring together epistemology, bibliographic memory, and database in the comprehension of research on Early Childhood Education policies as the first stage of Basic Education in Brazil. The concept of policy is mobilized to analyze education policy research focusing on early childhood care and to discuss, from an epistemological point of view, the consistency of the theoretical and methodological contributions adopted by researchers in this area of study. As a result of the analysis of authors and texts most cited in the database, three conceptual fields are indicated: broader studies that contribute to research in early childhood policies, such as Barroso (2005) and Mainardes (2006); studies that investigate policies for childcare, such as Kramer (1995) and Rosemberg (2002); and studies about policies for Early Childhood Education, such as Campos (1994) and Barreto (2003). In all three conceptual fields, the discussion and in-depth analysis from the Epistemologies of Education Policy Approach (EEPA) showed to be both relevant and adequate.Keywords: Policies. Early Childhood Education. Bibliographic Memory. Database. Epistemology.